2019
DOI: 10.1002/jcp.28382
|View full text |Cite
|
Sign up to set email alerts
|

Irisin ameliorates angiotensin II‐induced cardiomyocyte apoptosis through autophagy

Abstract: Cardiac hypertrophy is the main cause of heart failure and sudden death in patients. But the pathogenesis is unclear. Angiotensin II may contribute to cardiac hypertrophy in response to pressure overload. In angiotensin II‐treated cardiomyocytes, there is a larger cross‐sectional area, more apoptosis cells, and a reduction of irisin expression. An increase in P62, an autophagy flux index, as well as LC3II, were observed in cardiomyocytes after angiotensin II‐induced injury. Surprisely, irisin supplementation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Importantly, irisin administration significantly increased angiogenesis in the infarct border zone and decreased cardiomyocyte apoptosis but did not influence cardiomyocyte proliferation [106]. Accordingly, irisin has been shown to protect cardiomyocytes against apoptosis and dysfunction induced by different stressful stimuli, such as lipotoxicity [107], H 2 O 2 [108], hypoxia-reoxygenation [109,110], and doxorubicin-induced oxidative stress [111], as well as alleviating angiotensin-II-induced cardiac hypertrophy and fibrosis [15,112,113] and pressure overload-induced cardiac hypertrophy [114]. The induction of autophagy has been proposed as a mechanism though which irisin exerts these beneficial effects [112,114,115], as block of the autophagic flux has been identified as a possible cause of cardiomyocyte apoptosis and cardiac hypertrophy.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Importantly, irisin administration significantly increased angiogenesis in the infarct border zone and decreased cardiomyocyte apoptosis but did not influence cardiomyocyte proliferation [106]. Accordingly, irisin has been shown to protect cardiomyocytes against apoptosis and dysfunction induced by different stressful stimuli, such as lipotoxicity [107], H 2 O 2 [108], hypoxia-reoxygenation [109,110], and doxorubicin-induced oxidative stress [111], as well as alleviating angiotensin-II-induced cardiac hypertrophy and fibrosis [15,112,113] and pressure overload-induced cardiac hypertrophy [114]. The induction of autophagy has been proposed as a mechanism though which irisin exerts these beneficial effects [112,114,115], as block of the autophagic flux has been identified as a possible cause of cardiomyocyte apoptosis and cardiac hypertrophy.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The supplementation with irisin reduced cardiomyocytes apoptosis and increased autophagy, as ascertained by analysis of higher level of LC3II expression and decreased p62 expression, meanwhile, the autophagy inhibitor 3-MA reversed the protection exerted by irisin. In summary, the authors concluded that in animal model, overexpression of irisin alleviated myocardial hypertrophy induced by pressure overload reducing cardiomyocytes apoptosis and that irisin protection against pressure overload-induced cardiac hypertrophy is due to induction of protective autophagy and autophagy flux via activating AMPK-ULK1 signaling [ 166 ].…”
Section: Fndc5/irisin and Autophagymentioning
confidence: 99%
“…Irisin, a newly identified hormone, plays a vital role in regulating human body metabolism and oxidative stress, and several studies have reported the beneficial effects of irisin on cardiovascular disorders (Cheng et al 2018;Li et al 2019). In a model of murine ischemia reperfusion injury, irisin attenuates reperfusion-mediated heart damage through SOD1dependent mitochondrial protection (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%